2013
DOI: 10.1051/0004-6361/201220660
|View full text |Cite
|
Sign up to set email alerts
|

New companions in the stellar systems of DI Cha, Sz 22, CHXR 32, and Cha Hα5 in the Chamaeleon I star-forming region

Abstract: Context. The star-forming regions in Chamaeleon (Cha) are among the nearest (distance ∼165 pc) and youngest (age ∼2 Myr) conglomerates of recently formed stars and among the ideal targets for studies of star formation. Aims. We search for new, hitherto unknown binary or multiple-star components and investigate their membership in Cha and their gravitationally bound nature. Methods. We used the Naos-Conica (NACO) instrument at the Very Large Telescope Unit 4/YEPUN of the Paranal Observatory, at 2 or 3 different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 55 publications
(95 reference statements)
1
25
0
Order By: Relevance
“…To test the characterization of Glass Ib as a young star, we investigated the proper motions and modeled the SEDs of Glass Ia and Ib and found that the system is most likely associated with the Chameleon I star-forming region. Our models fit well with the SEDs using a G-type star for Glass Ib and a combined K-type and M-type to simulate a binary in Glass Ia (Schmidt et al 2013). Glass Ib also shows HCN, CO 2 , and H 2 O emission, which are commonly found in young stars (Pontoppidan et al 2010).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…To test the characterization of Glass Ib as a young star, we investigated the proper motions and modeled the SEDs of Glass Ia and Ib and found that the system is most likely associated with the Chameleon I star-forming region. Our models fit well with the SEDs using a G-type star for Glass Ib and a combined K-type and M-type to simulate a binary in Glass Ia (Schmidt et al 2013). Glass Ib also shows HCN, CO 2 , and H 2 O emission, which are commonly found in young stars (Pontoppidan et al 2010).…”
Section: Discussionmentioning
confidence: 60%
“…This in turn is inconsistent with the CO overtone absorption features at 2300 nm, which resemble a late K or early M dwarf. Schmidt et al (2013) do in fact resolve Glass Ia as a close double star in recent epochs of VLT/NACO AO images. Hence, Glass Ia could consist of an early to mid-K dwarf and an early M dwarf component, which would explain the spectral features we see.…”
Section: Optical Spectrummentioning
confidence: 84%
See 1 more Smart Citation
“…This object is a confirmed member of Chamaeleon I by Lopez Martí et al (2013) from proper motion studies. The best fit was obtained by including all the additional points listed above and with a value of A V much lower than the one reported in the literature (Luhman 2007;Schmidt et al 2013). No signs of the companion were found in the overall shape of the spectrum.…”
Section: B1 Chamaeleon I Targetsmentioning
confidence: 78%
“…Only the close binary at the center (Schmidt et al 2013) is included in the slit. This object is a confirmed member of Chamaeleon I by Lopez Martí et al (2013) from proper motion studies.…”
Section: B1 Chamaeleon I Targetsmentioning
confidence: 99%